MODIFIKASI ALAT SEMPROT PERTANIAN DENGAN SELANG PANJANG SEBAGAI UPAYA PENURUNAN KEJADIAN GANGGUAN MUSKULOSKELETAL PADA PETANI - Budiman, Erwanda Desire; Fristiyanwati, Yunita (Jurnal Pengabdian dan Kewirausahaan, 2023)
Ergonomics risk factors are the leading cause of musculoskeletal disorders experienced by workers. The results of a walkthrough survey that the authors conducted to see the processes carried out by rice farmers, starting from the nursery to the harvesting process, found that spraying had the highest ergonomic risk. The spraying activity involves lifting and carrying a reasonably heavy sprayer with a minimum capacity of 13 litres. The body must bend > 20⁰ to compensate for the burden on the back. This spraying activity is also accompanied by repetitive movements of the left arm when pumping the sprayer lever, an awkward position of the left arm raised >45⁰, and a static position of the right hand holding the nozzle stick to be directed to the field area. The results of this observation follow the author's findings when conducting health checks on farmer groups in Rorotan Village, Cilincing District, North Jakarta, who found that almost all farmers had musculoskeletal complaints, especially after spraying activities. This is the basis that it is necessary to intervene in this process to reduce musculoskeletal complaints experienced by farmers. The intervention was carried out by providing a modified electric sprayer with a polyurethane (PU) hose with a diameter of 6 mm and a length of 40 meters which aims to reduce lifting and carrying activities, repetitive movements, and awkward positions. To see the program's success, an assessment was carried out before and after the intervention, including the assessment of the body discomfort map, the Visual Analog Scale (VAS) for pain and comfort, and the REBA (Rapid Entire Body Assessment). The results of assessing farmers' subjective complaints using the body map discomfort questionnaire and the previous VAS decreased from 6.83 to 2.93, while the VAS value for comfort increased from 2.8 to 7.4. An objective assessment using REBA also found a decrease in the score from 10 to 3. To complement the program, education is also carried out to stretch every 2 hours of work and education on using proper and appropriate tools.